A leitura literária de discentes na biblioteca universitária da UERN - Santos, Andréia Lourenço dos (2021)
Reading literary texts can be considered one of the best ways to work with human language, at any stage of formal education. Much has been investigated about literary reading practices in elementary and high school, so, in our research, we seek to rescue the reading of literary texts in university students as a way to stimulate their creativity, imagination, open new interpretive horizons and assist the process of understanding their technical readings and their cognitive ability of oral and written linguistic expression. To this end, we evoke the responsibility of the University Library as a promoter of cultural and intellectual activities, especially reading, to disseminate Literature to future teachers in any teaching area. Our research turned to the analysis of the University Library as a place to promote the practice of literary reading. The research is based on the studies of Brito (2014, 2016), Milanesi (1983, 2013), Silva (1995, 1997, 1998, 2009), Souza (2005), Santos (2010), to understand the need to work with reading at the university, we will align with the reading visions of Silva (1995, 1997, 1998), Freire (1983), Chartier (1998, 2009), Pontes (2012), Pontes and Azevedo (2017) Santaella (2014), Colomer (2007), Manguel (2017), Jouve (212), among others. The research used the qualitative approach (BOGDAN and BIKLE, 2010), since our interest was to analyze the reality of literary reading performed by university students, in the context of the library, seeking to understand the reasons for its realization or lack of it. The subjects investigated were the students of undergraduate courses at the Central Campus and the servers of the central library. Documentary analysis of primary data sources was used (GIL, 2002), seeking to identify the available collection, as well as the number of loans for literary works carried out in 2019; in addition to the analysis of the official documents that govern the operation of the library at the IES. In order to verify the view of students and public servants as to whether or not to be a reader, their perception of literary reading at the university and the role of the library in this context, we applied a questionnaire addressing various items related to the analyzed problem, consisting of multiple questions choice and open-ended questions designed to collect each other's personal opinions. Our findings are potentially positive, since there are actions to encourage literary reading being developed by the investigated library and the students reveal themselves open to doing more of this type of reading, if there is enough, on the part of the library, institutionalization, expansion and dissemination of reading projects, either of their own or in partnership with academic departments